21st Annual BACUS Symposium on Photomask Technology 2002
DOI: 10.1117/12.458365
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact electrical critical dimensions metrology sensor for chrome photomasks

Abstract: This paper describes a novel non-contact capacitive-sensor metrology tool developed for chrome photomasks. This work further describes suitable types of test structures printed on photomasks appropriate for linewidth metrology. The Critical Dimension (CD) metrology sensor is developed using a Low Temperature Co-Fired Ceramic (LTCC) technology to reduce the effects of parasitic capacitances. The sensor is based on non-contact micro-capacitance measurements of features on chrome-on-glass reticles. The CD-extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous articles [8], [9] have shown that this algorithm can be constructed using conformal mapping techniques. These techniques, that map a problem of complex geometry into a problem of simpler geometry for which only a uniform homogeneous field reigns, allowed for determination of an equation linking the measured capacitance to the average width of the features (1) Referring to Figs.…”
Section: Sensor Calibrationmentioning
confidence: 99%
“…Previous articles [8], [9] have shown that this algorithm can be constructed using conformal mapping techniques. These techniques, that map a problem of complex geometry into a problem of simpler geometry for which only a uniform homogeneous field reigns, allowed for determination of an equation linking the measured capacitance to the average width of the features (1) Referring to Figs.…”
Section: Sensor Calibrationmentioning
confidence: 99%